2010
DOI: 10.1155/2010/628086
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of QoS Requirements for e-Health Services and Mapping to Evolved Packet System QoS Classes

Abstract: E-Health services comprise a broad range of healthcare services delivered by using information and communication technology. In order to support existing as well as emerging e-Health services over converged next generation network (NGN) architectures, there is a need for network QoS control mechanisms that meet the often stringent requirements of such services. In this paper, we evaluate the QoS support for e-Health services in the context of the Evolved Packet System (EPS), specified by the Third Generation P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 28 publications
0
68
0
1
Order By: Relevance
“…In WBANs, sensory data have their own characteristics due to different requirements in terms of delay, priority, packet loss, and other factors [27]. Thus, from the viewpoint of remote healthcare monitoring and important levels, we classify the WBAN traffic into emergency and normal traffic, which are defined as follows:…”
Section: Wban Traffic Categoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In WBANs, sensory data have their own characteristics due to different requirements in terms of delay, priority, packet loss, and other factors [27]. Thus, from the viewpoint of remote healthcare monitoring and important levels, we classify the WBAN traffic into emergency and normal traffic, which are defined as follows:…”
Section: Wban Traffic Categoriesmentioning
confidence: 99%
“…The data transmission time T data , back-off slots time T boff , and acknowledgement time T ack are given by the following equations [27]:…”
Section: Quality Of Service Attributes and User Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of 4G communication technologies on e-Health and the emerging challenges are discussed in [28]. In [29], a mapping between the QoS requirements of e-Health services and the existing service classes defined by 3GPP standards is proposed, aiming to provide guidelines for network operators. A cross-layer design for QoS of medical video streaming over mobile WiMAX (IEEE 802.16e) and High-Speed Packet Access (HSPA) 1 and a comparison between the performance of the two technologies is proposed in [30], opening 1 HSPA technology is a precursor to LTE.…”
Section: A Technology Integration For M2m Communicationsmentioning
confidence: 99%
“…Also a survey on QoS provisioning in wireless eHealth, handoff schemes for QoS support in wireless networks, the priority schemes for eHealth services and techniques/methods for IEEE 802.11 to guarantee QoS is also provided. A detailed analysis of QoS provision in eHealth services has been presented in [18], and it has been shown that eHealth services have diversified demands where the requirement of each application type vary with respect to context of use, type of service and the level of urgency. Authors in [19] proposed a methodology for the technical evaluation of QoS traffic requirement for telemedicine application, taking in to account application requirements, network topologies, and the evaluation of services using an automated tool.…”
Section: Introductionmentioning
confidence: 99%